2009
DOI: 10.3386/w15471
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Return to the High/Scope Perry Preschool Program

Abstract: This paper estimates the rate of return to the High/Scope Perry Preschool Program, an early intervention program targeted toward disadvantaged African-American youth. Estimates of the rate of return to the Perry program are widely cited to support the claim of substantial economic benefits from preschool education programs. Previous studies of the rate of return to this program ignore the compromises that occurred in the randomization protocol. They do not report standard errors. The rates of return estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
189
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(202 citation statements)
references
References 13 publications
3
189
1
9
Order By: Relevance
“…It is crucial to understand both cognitive skills and personality traits when assessing early-year educational investment on later labor market outcomes (Heckman, Moon, Pinto, Savelyev, & Yavitz, 2010). However, cognitive skills reach stability relatively early in life (Borghans et al, 2008), whereas personality traits continue to change throughout life, and, as demonstrated here, can do so in response to unemployment.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 75%
“…It is crucial to understand both cognitive skills and personality traits when assessing early-year educational investment on later labor market outcomes (Heckman, Moon, Pinto, Savelyev, & Yavitz, 2010). However, cognitive skills reach stability relatively early in life (Borghans et al, 2008), whereas personality traits continue to change throughout life, and, as demonstrated here, can do so in response to unemployment.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 75%
“…Additionally, studies of early interventions in the US have shown that such early intervention programmes are both cost effective and efficient. Heckman, Moon, Pinto, Savelyev & Yavitz (2009b) reported an estimated rate of return in the Perry Preschool Programme of between 7 and 10 percent. This suggests that providing early intervention in disadvantaged areas in Ireland may be an effective way of improving the overall level of school readiness in these areas and thus improve later outcomes for disadvantaged children.…”
Section: Resultsmentioning
confidence: 99%
“…It often takes intensive, closely targeted programmes with specific methods from a very early age to overcome disadvantage. For instance, some early childhood interventions among poor children in the United States -such as the Perry School Project 12 and, more recently, "Head Start" -have been found to have significant, durable effects on personality traits and social outcomes (Lee, 2008;Heckman et al, 2009). As Section 4 argues, there is also evidence that specialised interventions for adolescents from underprivileged backgrounds can improve skills and social and economic outcomes (also see Kautz et al, 2015).…”
Section: The Neet Challenge: What Can Be Done For Jobless and Disengamentioning
confidence: 99%